Weight or Density Corrected Value? Using Density Derived Key Ratio for Additional Accuracy to Intercomparability of Medieval and Historical Artifact Groups - Kinnunen Joonas (My University, 2022)
In this paper, I propose a method to improve the intercomparability of different artifact groups by narrowing the error caused by the differences in material densities. The products, especially of mixed materials, have not been previously analyzed as regards whether or not they have statistically significant differences in material densities or whether the densities affect comparative studies. The results showed that in addition to the obvious material groups like different metals and stones, there is also a significant difference in material densities when comparing redware and clay pipes by their weight. Therefore, the method presented here eliminates the effect of material density, but in a way that it is still intuitive and can be compared with values that have not been density corrected.